Enhanced-AODV: A Robust Three Phase Priority-Based Traffic Load Balancing Scheme for Internet of Things - Adil, Muhammad; Song, Houbing; Ali, Jehad; Jan, Mian Ahmad; Attique, Muhammad; Abbas, Safia; Farouk, Ahmed (IEEE Internet of Things Journal, 2022)
One of the operational challenges in the Internet of Things (IoT) is load balancing, which is the focus of interest of this article. We propose a three-phase enhanced ad hoc on-demand distance vector (enhanced-AODV) routing protocol for multiwireless sensor networks (multi-WSNs). The three phases are categorized based on traffic priority, namely: 1) high priority; 2) low priority; and 3) ordinary network traffic. The network architecture is divided into chains, i.e., local and public chains, where the cluster heads (CHs) and base stations (BSs) are used, respectively, to manage the network traffic based on priority information with alternative route allocation. Moreover, our three-phase enhanced-AODV protocol provides traffic categorization with alternatives route allocation to minimize energy consumption and prolong the lifetime of participating devices in the network. The proposed model is implemented in the simulation environment to overview results statistics in terms of network lifetime, prioritize traffic, computation and communication costs, latency, and packet lost ratio (PLR). Findings from the simulation suggest that our scheme achieves 15% improvement in network lifetime, 17% latency, 22% PLR, and approximately 10% in the computation and communication costs of the network, in comparison to three other similar protocols.
Keywords: Ad hoc on demand distance vector; Alternative routes; Communication cost; Internet of thing (IOT); Network lifetime; Operational challenges; Simulation environment; Traffic priorities; Enhanced ad hoc on-demand distance vector (enhanced-AODV) scheme; Internet of Things (IoT); load balancing; local chain; multiwireless sensor networks (multi-WSNs); network lifetime; public chain